(untitled) (Eduscotech, 2019)
This study aims to determine whether the learning model numbers quiz TGT smart strategy to be effective against the ability of the representation. The population in this study were of class VII junior high school 3 Kudus. Obtained by random sampling technique three classes were randomly as the sample is a class VII H as experimental class 1, VII G as the experimental class 2 and VII I as a class control. The data was collected with the test method. Based on the analysis of survey results revealed that 89% of students who were taught using the learning model numbers quiz TGT smart strategy to achieve exhaustiveness study. Of ANAVA test, the average difference between smart strategy learning model number quiz TGT, TGT and expository learning model. From the test results obtained up to sceffe representation ability of learners who are taught by learning model numbers quiz TGT smart strategy is better than being taught by TGT learning model and representation capabilities of learners who are taught by TGT learning model is better than being taught to use expository learning. From the above description it can be concluded that the learning smart numbers quiz TGT strategy to be effective against the ability of the representation high quadrilateral material of class VII junior high school 3 kudus.